When stereotype threat does not impair performance, self-affirmation can be harmful. Issue 3 (4th May 2019) - Voisin, Dimitri; Brick, Cameron; Vallée, Boris; Pascual, Alexandre
Abstract: When an individual is threatened by a negative stereotype, they are motivated to disconfirm the stereotype to protect self-integrity. When the task is simple and short, this motivation enables threatened individuals to counter the harmful effects of stereotype threat. Two theoretical accounts could explain this effect. First, performance is facilitated by a correct prepotent response according to the mere effort account. Second, the threatened individuals adopt a prevention focus that has a beneficial effect if the task demands few cognitive resources. The present article tested the hypothesis that protecting self-integrity via self-affirmation reduces the motivation to disconfirm the stereotype and could therefore harm performance. Across two experiments, threatened participants performed worse on simple and short math (Study 1) and mental rotations (Study 2) tests when self-affirmed compared to control. When stereotype threat leads to motivated engagement with a task, self-affirmation can reduce that motivation by boosting self-integrity.